Primary care physicians' attitudes, practices, and perceived barriers toward depression screening in older people in the Kingdom of Bahrain - Habbash, Fatema; Khamis, Zainab; Alasfoor, Zahra; Mahdi, Aayat; Alsharkhat, Masooma; Hasan, Noor; Al Qari, Alaa; Chlif, Sadok; Almarabheh, Amer; Ben Salah, Afif (Frontiers in Medicine, 2024)
Purpose This study aimed to explore attitudes, practices, and perceived barriers of primary care physicians (PCPs) toward depression screening in older people. Methods This cross-sectional study enrolled PCPs from randomly selected representative primary care centers in Bahrain. A self-administered piloted semi-structured questionnaire was used for data collection. Results We enrolled 248 PCPs in the study (82.3% females, and the mean age = 40 ± 8.7 years). More than half of the participants (54.4%) had a positive attitude toward depression screening in older people. However, only 10.9% of the participants reported systematically screening for this condition without using specific tools for screening in 45.5%. The most reported barriers toward this service are short consultation time (95%), the presence of multiple co-morbidities in this age group (90%), and the absence of guidelines or appropriate training in around 30%. Positive attitudes were significantly higher among older PCPs (p = 0.039), family physician consultants (p = 0.008), those with more than 10 years of work experience (p = 0.024), and those who participated in related educational activities (p = 0.007). Under-screening practice is associated with perceived short consultation time (p = 0.002), insufficient continuous medical education (CME) activities attendance in older people's mental health (p = 0.048) as well as having a general physician's title (p = 0.049). Only the PCPs' job title, Adjusted Odds Ratio (OR) = 3.513, 95 C.I [1.225-10.074] and attendance of CME activities, OR = 1.278, 95 C.I [1.098 – 3.192] remained significant when controlled for age and experience. Conclusion More training on older people's mental health and provision of screening and management guidelines are priorities to promote older people's mental health in primary care settings.